The sacral networks and neural pathways used to elicit lumbar motor rhythm in the rodent spinal cord - Cherniak, Meir; Etlin, Alex; Strauss, Ido; Anglister, Lili; Lev-Tov, Aharon (Frontiers in Neural Circuits, 2014)
Identification of neural networks and pathways involved in activation and modulation of spinal central pattern generators (CPGs) in the absence of the descending control from the brain is important for further understanding of neural control of movement and for developing innovative therapeutic approaches to improve the mobility of spinal cord injury patients. Activation of the hindlimb innervating segments by sacrocaudal afferent input and by specific application of neurochemicals to the sacral networks is feasible in the isolated spinal cord preparation of the newborn rat. Here we review our recent studies of sacral relay neurons with lumbar projections and evaluate their role in linking the sacral and thoracolumbar networks during different motor behaviors. Our major findings show that: 1) Heterogeneous groups of dorsal, intermediate and ventral sacral-neurons with ventral and lateral ascending funicular projections mediate the activation of the locomotor central pattern generators through sacral sensory input, and 2) Rhythmic excitation of lumbar flexor motoneurons, produced by bath application of alpha-1 adrenoceptor agonists to the sacral segments is mediated exclusively by ventral clusters of sacral-neurons with lumbar projections through the ventral funiculus.